Association of aescin with β- and γ-cyclodextrins studied by DFT calculations and spectroscopic methods - Ramos, Ana I.; Vaz, Pedro D.; Braga, Susana S.; Silva, Artur M. S. (Beilstein Journal of Nanotechnology, 2017)
Background: Aescin, a natural mixture of saponins occurring in Aesculus hippocastanum, exhibits important flebotonic properties, being used in the treatment of chronic venous insufficiency in legs. The inclusion of aescin into cyclodextrins (CDs) is a technical solution for its incorporation into the textile of stockings, but details of the physicochemistry of these host–guest systems are lacking. This work investigates the inclusion of aescin into the cavities of two native cyclodextrins, β-CD and γ-CD.Results: The continuous variation method applied to aqueous-phase 1H nuclear magnetic resonance (1H NMR) has demonstrated that the preferred CD/aescin inclusion stoichiometries are 2:1 with β-CD and 1:1 with γ-CD. The affinity constant calculated for γ-CD·aescin was 894 M−1, while for 2β-CD·aescin it was estimated to be 715 M−1. Density functional theory (DFT) calculations on the interaction of aescin Ib with CDs show that an inclusion can indeed occur and it is further demonstrated that the wider cavity of γ-CD is more adequate to accommodate this large guest. ROESY spectroscopy is consistent with the formation of a complex in which the triterpenic moiety of aescin is included into the cavity of γ-CD. The higher stability of this geometry was confirmed by DFT. Furthermore, DFT calculations were applied to determine the chemical shifts of the protons H3 and H5 of the CDs in the optimised structures of the inclusion complexes. The calculated values are very similar to the experimental data, validating the approach made in this study by NMR.Conclusion: The combination of experimental data from aqueous-state NMR measurements and theoretical calculations has demonstrated that γ-CD is the most suitable host for aescin, although the inclusion also occurs with β-CD. The geometry of the γ-CD·aescin complex is characterised by the inclusion of the triterpene segment of aescin into the host cavity.
Keywords: aescin; cyclodextrin inclusion; DFT; 1H NMR; ROESY